STUDIO ANIMASI DI BANJARMASIN - Ulfatana, Yuni Annisa; Wastuty, Prima Widia (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
An animation studio is an animation production site. However, their products and functions are still not widely known by the public, so there are still few users of their services. The animation is not only entertainment media but also as an intermediary media that can facilitate an activity. So an attractive and interactive animation studio is needed. The solution offered is to use a simulation method that aims to make it easier for people to understand animation. Simulation is a method that shows something in a simulant form that is similar to the real situation. This method uses the Triadic Game Design approach that has three aspects, namely play, meaning, and reality. These three aspects are used as references in the animation studio.